Experimental and numerical investigation of the effect of turbulent inflow on a Horizontal Axis Wind Turbine (Part I: Power performance). (15th October 2016) - Li, Qing'an; Murata, Junsuke; Endo, Masayuki; Maeda, Takao; Kamada, Yasunari
Abstract: This study aimed to analyze the effect of turbulence intensity and wind shear on the power characteristics of a Horizontal Axis Wind Turbine (HAWT). For this purpose, the blade pitch angle and yaw were compared by using a two-bladed HAWT in the wind tunnel experiments. In this study, the turbulence intensities were generated by active turbulence grids and wind shears were obtained by an atmospheric boundary layer generation device. Through measurement of the power and thrust coefficients for each rotor configuration, the aerodynamic feasibility of this wind turbine was discussed. As a result, it was clarified that the power coefficient was strongly dependent on the blade pitch angle and yaw angle. The optimum power coefficients were 0.308, 0.321, 0.298 at the blade pitch angle of β = 4°, for the turbulence intensities of TI = 1.4%, 8.0% and 13.5%. Moreover, thrust coefficient decreased with the increase of pitch angle. For the optimum pitch angle, the maximum power and thrust coefficients obtained at a s = 0.0558, showing smaller values than the results of wind shear a s = 0.1447. From this study, these results were very important for developing HAWT suitable for turbulence environment. Highlights: Power performance was measured at different turbulence intensities and wind shears. Effects of blade pitch angle and yaw angle were compared. Peak of the power coefficient decreased with the increase of yaw angle. Thrust coefficient decreased with the increase of pitch angle. Wind shear had a significant effect on the power and thrust coefficients.